2007
DOI: 10.1111/j.1365-2745.2007.01216.x
|View full text |Cite
|
Sign up to set email alerts
|

Greater capacity for division of labour in clones of Fragaria chiloensis from patchier habitats

Abstract: Summary1 Unlike non-clonal plants, clonal plants can develop a division of labour in which connected ramets specialize to acquire different, locally abundant resources. This occurs as a plastic response to a patchy environment where two resources tend not to occur together and different ramets experience high availabilities of different resources. We hypothesized that if division of labour is an important advantage of clonal growth in such environments in nature, then clones from habitats where resource availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
99
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 37 publications
8
99
0
1
Order By: Relevance
“…However, higher availability of nitrogen in the N + L-sector might support physiological compensation (Mooney and Winner 1991). Roiloa et al (2007) recently showed that not only biomass investments may be responsible for capturing a limiting resource in clonal plants in a heterogeneous environment, but physiological compensation may play a role as well. Therefore, we can speculate that there can be higher nitrogen concentration or higher concentration of chlorophyll in leaves and physiological plasticity could lead to enhanced photosynthesis in the shaded sector (N + L-).…”
Section: Discussionmentioning
confidence: 99%
“…However, higher availability of nitrogen in the N + L-sector might support physiological compensation (Mooney and Winner 1991). Roiloa et al (2007) recently showed that not only biomass investments may be responsible for capturing a limiting resource in clonal plants in a heterogeneous environment, but physiological compensation may play a role as well. Therefore, we can speculate that there can be higher nitrogen concentration or higher concentration of chlorophyll in leaves and physiological plasticity could lead to enhanced photosynthesis in the shaded sector (N + L-).…”
Section: Discussionmentioning
confidence: 99%
“…However, under homogeneous resource conditions the benefits of sharing are suggested to decrease or to be turned into a cost (Pitelka and Ashmun 1985;Caracao and Kelly 1991;Alpert 1999). Both theoretical and empirical studies suggest that selection for a higher degree of resource sharing occurs in habitats where resources are heterogeneously distributed, resulting in local adaptation for resource sharing (Alpert 1999;Oborny et al 2000;Alpert et al 2003), or division of labour (Roiloa et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…When remaining intact, stolon internodes play important roles in clones' foraging responses (Birch and Hutchings 1994;Wijesinghe and Hutchings 1999) and resource sharing (Alpert 1999;Alpert et al 2003), thereby contributing greatly to their fitness (Alpert 1999;van Kleunen and Stuefer 1999;Alpert et al 2003;Roiloa et al 2007;Wang et al 2008;Yu et al 2009). …”
Section: Introductionmentioning
confidence: 98%